Normal values of plasma fibrinogen in Cebus apella monkeys iunder ketamine anesthesia - Molina, Silvio Ricardo; Larsson Junior, Carlos Eduardo; Mirandola, Regina Mieko Sakata; Larsson, Maria Helena Matiko Akao; Fedullo, José Daniel Luzes; Birgel, Eduardo Harry (Brazilian Journal of Veterinary Research and Animal Science, 1997)
Normal values of plasma fibrinogen were determined in 108 Cebus apella monkeys. This parameter was studied in 53 males (12 young and 45 adults) and 55 females (20 young and 35 adults). Blood was collected through venipuncture of right and/or left femoral vein from animals under ketamine sedation (10 mg/kg, intramusculary administred). Determination of fibrinogenemia was done according to the technique described by Schalm et al. (1975). Results are expressed in mg/dl.